Zukunft der deutschen Energiegenossenschaften: Herausforderungen und Chancen aus einer Innovationsperspektive - Klagge, Britta; Schmole, Hanna; Seidl, Irmi; Schön, Susanne (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Energy co-operatives have played an important role in the development of decentralized renewable electricity production in Germany in the new millennium. They collect capital from individuals and thus open up another source of funding to promote the ”Energiewende“ in Germany. Their regional orientation and the co-operative participation model are regarded as success factors which help to increase local acceptance. With the amendment of the German Renewable Energy Sources Act (EEG) in 2014, the so far very favorable funding conditions gradually fall away, which were central to the business models of many, especially regional energy co-operatives. The boom phase of energy co-operatives has thus come to an end and the increasing market orientation of support policies requires adaptations and innovations. Against this background the paper explores energy cooperatives and their development from an innovation perspective. It specifically asks how they need to position, if they are to make a significant contribution to a decentralized energy transition in the future. In the empirical part of this paper, we examine the structures and developments in the German energy co-operative sector based on existing data and an online survey, with a focus on energy cooperatives of different sizes and geographical orientation, complemented by an analysis of two case studies. We conclude that economies of scale and geographical diversification can offer benefits, but that there are also promising development opportunities for regional energy co-operatives. Diversification of business fields, which can include not only energy-related services, but also other local general interest services, as well as cooperation at the regional level and with other energy co-operatives and their umbrella associations, could be starting points for successful regional strategies. In general, direct marketing can become a potentially important element of innovative development of business models, because – in accordance with the co-operative core principles of member orientation and the principle of identity – it links the focus on specific target groups with a regional or ideological surplus value.